Evaluation of Xylella fastidiosa genetic diversity by fAFLP markers - Kishi, Luciano Takeshi [UNESP]; Wickert, Ester [UNESP]; Lemos, Eliana Gertrudes De Macedo [UNESP] (FapUNIFESP (SciELO), 2008)
The first phytopathogenic bacterium with its DNA entirely sequenced is being detected and isolated from different host plants in several geographic regions. Although it causes diseases in cultures of economic importance, such as citrus, coffee, and grapevine little is known about the genetic relationships among different strains. Actually, all strains are grouped as a single species, Xylella fastidiosa, despite colonizing different hosts, developing symptoms, and different physiological and microbiological observed conditions. The existence of genetic diversity among X. fastidiosa strains was detected by different methodological techniques, since cultural to molecular methods. However, little is know about the phylogenetic relationships developed by Brazilian strains obtained from coffee and citrus plants. In order to evaluate it, fAFLP markers were used to verify genetic diversity and phylogenetic relationships developed by Brazilian and strange strains. fAFLP is an efficient technique, with high reproducibility that is currently used for bacterial typing and classification. The obtained results showed that Brazilian strains present genetic diversity and that the strains from this study were grouped distinctly according host and geographical origin like citrus-coffee, temecula-grapevine-mulberry and plum-elm.
Keywords: DNA fingerprinting; fAFLP; Genetic diversity; Xylella fastidiosa